The effect of fluoride varnish and chlorhexidine gel on white spots and gingival and plaque indices in fixed orthodontic patients: A placebo-controlled study - Shiva Alavi; Navid Yaraghi (Wolters Kluwer Medknow Publications, 2018)
Background: Difficulties to maintain good oral hygiene during orthodontic treatment can cause prolonged accumulation of dental plaque, thereby increasing the risk of developing gingival inflammation and periodontal disease as well as enamel demineralization and caries. The purpose of this study was to determine the effect of chlorhexidine (CHX) gel and fluoride varnish versus placebo and control groups on plaque and gingival indices as well as their influence on enamel demineralization prevention in orthodontic patients with fixed appliances. Materials and Methods: In this clinical trial, forty patients with fixed orthodontic appliances were participated and were divided into control, CHX gel (0.2%), fluoride varnish (5%), and placebo groups. The parameters evaluated in this research were dental plaque index (DPI), index of gingival inflammation, and white spot lesion (WSL) index. For all the patients, each index was scored at the beginning of orthodontic treatment, then 3 months, 6 months, and 9 months afterward. Data were analyzed using Kruskal-Wallis and Mann-Whitney tests. The level of significance was set at 0.05. Results: All the scores showed statistically significant differences (P < 0.05) between the four groups for each of the three time points. A statistically significant decrease of DPI, WSL index, and gingival index was observed 9 months after treatment in fluoride and CHX groups. Conclusion: Adding CHX gel and fluoride varnish to the patients' oral hygiene regimen can reduce the development of plaque and gingivitis and decrease WSLs in orthodontic patients.